HUBUNGAN RIWAYAT INISIASI MENYUSUI DINI DENGAN KEJADIAN DIARE PADA BAYI 0-6 BULAN DI SUMATERA UTARA: ANALISIS DATA SURVEI DEMOGRAFI DAN KESEHATAN INDONESIA (SDKI) 2017 - Kandita Iman Khairina (Jurnal Medika Hutama, 2023)
Diarrhea is one of post-natal and under five year old causes of death in Sumatera Utara, 12,55% in 2019 and 10,82% in 2020. Diarrhea prevalence in 0-5 month infants in Sumatera Utara. Erly breastfeeding initiation is one of the protective factors of diarrhea. Early breastfeeding initiation in 0-6 month infants in Sumatera Utara is 41,52% in 2018. This study is a descriptive study with cross-sectional approach using secondary data from Indonesia Demography and Health Survey 2017. Samples are infants aged 0-6 month old with no physical disability. Total of infants that are included in the study is 102 infants. Analysis that will be used in the study is univariate and bivariate. Bivariate analysis using chi-square test. This study shows prevalence of diarrhea in 0-6 infants are 11,8% and early breastfeeding initiation is 14,7%. Bivariate analysis shows that there is no significant association between early breastfeeding initiation and diarrhea. Mother needs to be educated about the benefits of early breastfeeding initiation.